2016
DOI: 10.1371/journal.pone.0149186
|View full text |Cite
|
Sign up to set email alerts
|

A Randomised Controlled Trial of Therapist-Assisted, Internet-Delivered Cognitive Behavior Therapy for Women with Maternal Depression

Abstract: Postpartum depression impacts up to 15% of Canadian women following childbirth. Remarkably, many women suffering from this disorder do not receive appropriate treatment. The aim of this study was to conduct a parallel-group randomized controlled trial to determine the efficacy of Therapist-Assisted Internet-delivered Cognitive Behavior Therapy (TA-ICBT) for the treatment of postpartum depression. This study was registered with the International Standard Randomized Controlled Trials (ISRCTN: 85456371) and recei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
126
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 88 publications
(130 citation statements)
references
References 48 publications
4
126
0
Order By: Relevance
“…We also compared imbPST to studies of face-to-face psychotherapy (Agnew-Davies, Stiles, Hardy, Barkham, & Shapiro, 1998) and the CB therapy program BtB (Ormrod et al, 2010) on their ability to develop therapeutic alliance. We found that imbPST creates a strong therapeutic alliance equivalent to face-to-face psychotherapy (Berman et al, 2014), consistent with previous CB therapy literature (Andersson et al, 2012; Kiropoulos et al, 2008; Knaevelsrud & Maercker, 2006, 2007; Pugh, Hadjistavropoulos, & Dirkse, 2016; Sucala et al, 2012). Despite these promising findings, to date imbPST has not been subjected to a randomized controlled trial.…”
supporting
confidence: 90%
“…We also compared imbPST to studies of face-to-face psychotherapy (Agnew-Davies, Stiles, Hardy, Barkham, & Shapiro, 1998) and the CB therapy program BtB (Ormrod et al, 2010) on their ability to develop therapeutic alliance. We found that imbPST creates a strong therapeutic alliance equivalent to face-to-face psychotherapy (Berman et al, 2014), consistent with previous CB therapy literature (Andersson et al, 2012; Kiropoulos et al, 2008; Knaevelsrud & Maercker, 2006, 2007; Pugh, Hadjistavropoulos, & Dirkse, 2016; Sucala et al, 2012). Despite these promising findings, to date imbPST has not been subjected to a randomized controlled trial.…”
supporting
confidence: 90%
“…[71][72][73] An increasing body of evidence also supports the use of therapist-assisted Internet-based behavioural activation and CBT, whereas the effectiveness of unsupported Internet-based psychotherapeutic interventions has not been established. [74][75][76] While not extensively studied in the postpartum period, mindfulnessbased CBT and supportive, couples, and psychodynamic psychotherapy may have a role for selected women.…”
Section: How Is Depression Treated During the Postpartum Period?mentioning
confidence: 99%
“…All of the studies were conducted between 2011 [47] and 2016 [31], with 2016 having the highest number of publications (38%, 3/8) [28,29,31]. …”
Section: Resultsmentioning
confidence: 99%
“…Contrary to previous findings on the equivalent effect of support type for stress symptoms in a meta-analytic review [13], our finding showed that exclusive therapist support has a better effect than therapist support with self-care component in the subgroup analysis. A possible interpretation of this result is that the different attrition rates reached 2.9%–60.8% by therapist support with self-care components [28,32,33] compared with the 7.0%–31.3% rates by exclusive therapist support [29-31,46,47]. This finding supported the fact that exclusive therapist support was preferred to reduce stress symptoms, whether by phone, email, text, or interactive computer interface [10,11].…”
Section: Discussionmentioning
confidence: 99%